Interfering amino terminal peptides and functional implications for heteromeric gap junction formation - Veenstra, Richard D.; Lin, Xianming; Beyer, Eric C. (Frontiers in Pharmacology, 2013)
Connexin43 (Cx43) is widely expressed in many different tissues of the human body. In cells of some organs, Cx43 is co-expressed with other connexins (Cx), including Cx46 and Cx50 in lens, Cx40 in atrium, Purkinje fibers, and the blood vessel wall, Cx45 in heart, and Cx37 in the ovary. Interactions with the co-expressed connexins may have profound functional implications. The abilities of Cx37, Cx45, Cx46, and Cx50 to function in heteromeric gap junction combinations with Cx43 are well documented. Different studies disagree regarding the ability of Cx43 and Cx40 to produce functional heteromeric gap junctions with each other. We review previous studies regarding the heteromeric interactions of Cx43. The possibility of negative functional interactions between the cytoplasmic pore-forming amino terminal (NT) domains of these connexins was assessed using pentameric connexin sequence-specific NT domain (iNT) peptides applied to cells expressing homomeric Cx40, Cx37, Cx45, Cx46, and Cx50 gap junctions. A Cx43 iNT peptide corresponding to amino acids 9 to 13 (Ac-KLLDK-NH2) specifically inhibited the electrical coupling of Cx40 gap junctions in a transjunctional (Vj) voltage-dependent manner without affecting the function of homologous Cx37, Cx46, Cx50, and Cx45 gap junctions. A Cx40 iNT (Ac-EFLEE-OH) peptide counteracted the Vj-dependent block of Cx40 gap junctions, whereas a similarly charged Cx50 iNT (Ac-EEVNE-OH) peptide did not, suggesting that these NT domain interactions are not solely based on electrostatics. These data are consistent with functional Cx43 heteromeric gap junction formation with Cx37, Cx45, Cx46, and Cx50 and suggest that Cx40 uniquely experiences functional suppressive interactions with a Cx43 NT domain sequence. These findings present unique functional implications about the heteromeric interactions between Cx43 and Cx40 that may influence cardiac conduction in atrial myocardium and the specialized conduction system.